การบริหารพัสดุตามหลักธรรมาภิบาลของผู้บริหารสถานศึกษาสังกัด สำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 - ผายภักดิ์, ลัดดาวัลย์; ชนะโยธา, พรทิวา (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด, 2023)
การวิจัยครั้งนี้มีวัตถุประสงค์ 1) เพื่อศึกษาการบริหารพัสดุตามหลักธรรมาภิบาล ของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 2) เพื่อเปรียบเทียบการบริหารพัสดุตามหลักธรรมาภิบาลของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 จำแนกตามตำแหน่ง ระดับการศึกษา ประสบการณ์ทำงาน   3) เพื่อศึกษาแนวทางการบริหารงานพัสดุตามหลักธรรมาภิบาลของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 กลุ่มตัวอย่าง ได้แก่ ผู้บริหารและครู จำนวน 351 คนและผู้ให้สัมภาษณ์ 5 คน เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถามแบบมาตราส่วนประมาณค่า 5 ระดับ มีค่า IOC ระหว่าง 0.67-1.00 มีค่าความเชื่อมั่นทั้งฉบับ เท่ากับ 0.796 และแบบสัมภาษณ์กึ่งโครงสร้าง สถิติที่ใช้ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน สถิติทดสอบค่าที (t-test) และสถิติการวิเคราะห์ความแปรปรวนทางเดียว F-test (One-Way ANOVA) ผลการวิจัยพบว่า 1. การบริหารพัสดุตามหลักธรรมาภิบาลของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 โดยรวมอยู่ในระดับมาก ด้านที่มีค่าเฉลี่ยสูงสุด ได้แก่ ด้านการเก็บ การบันทึก การเบิกจ่าย รองลงมาคือ ด้านการยืม ส่วนด้านที่มีค่าเฉลี่ยต่ำสุด คือ ด้านการจำหน่าย 2. ผลการเปรียบเทียบการบริหารพัสดุตามหลักธรรมาภิบาลของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 จำแนกตามตำแหน่ง ระดับการศึกษา แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และจำแนกตามประสบการณ์ทำงาน ไม่แตกต่างกัน 3. ข้อเสนอแนะแนวทางการบริหารพัสดุตามหลักธรรมาภิบาลของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 2 จากการศึกษาผู้บริหาร ครูที่ปฏิบัติงานพัสดุ พบว่าแนวทางการบริหารงานพัสดุตามหลักธรรมาภิบาลของผู้บริหารสถานศึกษา มีทั้งหมด 15 แนวทาง แยกเป็นรายด้านดังนี้ 1) ด้านการเก็บ การบันทึก การเบิกจ่าย มี 4 แนวทาง 2) ด้านการยืม มี 5 แนวทาง 3) ด้านการบำรุงรักษา การตรวจสอบ มี 3 แนวทาง 4) ด้านการจำหน่าย มี 3 แนวทาง The purposes of this research were 1) to study supply management based on the Principles of Good Governance of Educational institution administrators under Roi Et Primary  Educational Service Area office 2   2)  to compare supply management based on the Principles of Good Governance of Educational institution administrators under  Roi Et Primary Educational Service Area office 2, classified by positions, education and working experiences, and 3) to study the guidelines for supply management based on the Principles of Good Governance of Educational institution administrators under Roi Et Primary  Educational Service Area office 2.  The sample group in this research was 351 school administrators and teachers and 5 interviewees. The research instruments were a 5-point estimating scale questionnaire with an IOC between 0.67-1.00 with a confidence level of 0.796 and a semi-structured interview. The statistics used were frequency, percentage, mean, and standard deviation, t-test and F-test (One-Way ANOVA) analysis of variance. The results showed that: 1. Supply management based on the principles of Good Governance of Educational institution administrators under Roi Et Primary Educational Service Area office 2, overall was at a high level. The aspect with the highest average was storage, recording, disbursement followed by borrowing, and the aspect with the lowest average was distribution. 2. The comparison results of supply management based on the Principles of Good Governance of Educational institution administrators under Roi Et Primary Educational Service Area office 2, classified by position, education level, the difference was statistically significant at the .05 level. And there was no difference when classified by work experiences. 3. Recommendations for the supply management based on the Principles of Good Governance of Educational institution administrators under Roi Et Primary Educational Service Area office 2, from the educational institution administrators, Teachers who performs supplies found that there were a total of 15 guidelines for  supply management based on the Principles of Good Governance for educational institute administrators, separated by aspects as follows: 1)Storage, Recording, disbursement, there were 4 approaches 2) Borrowing, there were 5 approaches 3) Maintenance and Inspection, there were 3 approaches 4) Distribution, there were 3 approaches.